Does Preoperative Mixed‐Growth Urine Culture Increase the Risk of Urinary Tract Infection After Ureteroscopic Stone Treatment? A Retrospective Study - Khalid Elsayed Mahmoud; Ahmad R. Al‐Qudimat; Ahmed Khaled Alhusban; Raed M. Al‐Zoubi; Mai Elaarag; Abdulkader Alobiedly; Ibrahim A. khalil; Abdulla AlAnsari (Health Science Reports, 2026)
ABSTRACT Background Ureteroscopy (URS) has emerged as a leading treatment option for urinary stones, with its usage growing from 30% to 70% over the last 20 years. Post‐URS complications, particularly infectious issues like UTIs, remain a concern, occurring in up to 25% of cases. This study aims to explore the relationship between preoperative mixed‐growth urine culture and postoperative outcomes of URS, addressing a critical gap in understanding the value and influence of these cultures. Methodology This retrospective study included adult patients (18–65 years) who underwent RIRS or R‐URS for ureteral or renal stones at a tertiary care center between January 1, 2020, and May 1, 2024. Patients were categorized by preoperative urine culture (no growth vs. mixed growth), and consecutive cases were included until equal group sizes were achieved. Univariable and multivariable logistic regression were used to identify factors associated with mixed growth and to evaluate outcomes related to mixed growth. Results The cohort included two equal‐sized groups ( n = 73 each) based on urine culture results. The cohort comprised 52.05% males and 47.95% females. The mixed growth group exhibited significantly lower hemoglobin levels ( p < 0.001) and higher bacterial counts ( p < 0.001). ICU admission showed a trend toward significance ( p = 0.08), while other factors like pre‐stented ureters ( p = 0.09) and type of surgery ( p = 0.092) did not reach significance. Mixed bacterial growth on urine culture was associated with significantly higher rates of postoperative UTI (17.8% vs. 2.7%, p = 0.003), readmission (17.8% vs. 0%, p < 0.001), and fever (15.1% vs. 0%, p < 0.001), with a non‐significant increase in ICU admission (4.1% vs. 0%, p = 0.08). Male gender was independently associated with a lower likelihood of mixed bacterial growth (OR = 0.25, 95% CI: 0.11–0.52, p = 0.001), whereas mixed growth was associated with increased odds of postoperative UTI on univariate analysis. Conclusion Mixed bacterial growth on preoperative urine culture is associated with a higher risk of postoperative infectious complications following RIRS and R‐URS. Female patients appear to be at higher risk for mixed growth, highlighting the importance of careful preoperative assessment and targeted perioperative management to optimize outcomes.